Long-Term Grazing Exclusion Reduces Species Diversity but Increases Community Heterogeneity in an Alpine Grassland - Song, Shanshan; Zhu, Jiangling; Zheng, Tianli; Tang, Zhiyao; Zhang, Fan; Ji, Chengjun; Shen, Zehao; Zhu, Jianxiao (Frontiers in Ecology and Evolution, 2020)
Extensive grazing activity is threatening the alpine grassland on the Qinghai-Tibetan Plateau. Evidence showed that grazing exclusion may change the composition, structure and functions of grassland ecosystems. However, such effects depends on the intensity and duration of exclusion. We explored the effects of short-term (2 and 4 years) and long-term (9 and 11 years) grazing exclusion on plant height, coverage and diversity and community heterogeneity in the alpine grassland on the Qinghai-Tibetan Plateau. We found no difference in plant diversity between the short-term grazing exclusion and control. However, long-term grazing exclusion reduced species richness and increased the Simpson dominance index. This decrease in plant species richness mainly contributed to the decrease in common species richness (defined as species with a relative coverage of 1~5%). In addition, community heterogeneity (coefficient of variation, CV) was significantly higher in the long-term grazing exclusion than in the controlled plots. A structural equation modeling (SEM) demonstrated that long-term grazing exclusion increased the community heterogeneity mainly by reducing species diversity. These results suggest that the effects of grazing exclusion on the composition, structure and community spatial heterogeneity of the alpine grassland ecosystem are dependent on the exclusion duration. Grazing activity may maintain high biodiversity and community stability of the alpine grassland in the harsh environment of the Qinghai-Tibetan Plateau.